Representasi Eksistensi Perempuan Dalam Film Wadjda Karya Haifaa Al - Mansour: (Kajian Feminisme Eksistensialis Simone De Beauvoir) - Triyani, Ebet; Choironi, Merry; Rahmawati, Isnaini (Kitabina: Jurnal Bahasa dan Sastra, 2023)
Abstract This study aims to determine the form of women’s existence and the efforts of women’s struggle to realize their existence contained in the film Wadjda by Haifaa Al-Mansour. The theory used in this study is Simone De Beauvoir’s existentialist feminist theory. While the approach uses a qualitative literary approach with more emphasis on the meaning of freedom and certain values. To achieve this, the researvher uses a qualitative descriftive analysis method. The findings of this study are as followa : 1) The existence of women through destiny which consist of 2 scenes, 2) The existence of women through history consist of 7 scenes, and 3) The existence of women thriugh myths consist of 3 scenes. In addition to these three forms of existence, the results of the analysis of women’s efforts to exist in this film are : 1)Accepting oneself as an other figure which is depicted through women in love, narcissistic women, and mystical women with a total of 4 scenes, then 2) Women who refuse to be others by working, become intelectual. Refuse to be subordinate to men, and achieve social transformation with a total of 10 scenes.